K-band waveguide T-junction diplexer for satellite communication - H. Setti; A. Tribak; A. El Hamichi; J. Zbitou; A. Mediavilla (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Design and measurement of two waveguide diplexers on H-plane T-junction, are presented. The two diplexers structures consist of a waveguide H-plane T-junction and two waveguide obtained cavity filters. The two diplexers operate in the same frequency bands (17 GHz-19.5 GHz). The simulation results show that over the operating band of two filters, the return losses are better than 18 dB and insertion losses are lower than 0.05 dB. The proposed diplexers have been simulated using Mician μ Wave Wizard simulator based on the mode matching method (MMM). The diplexers have been validated experimentally and results are presented. Simulated and measured results show good agreement.